Analysis and Synthesis of Switched Time-Delay Systems: The Average Dwell Time Approach - Zhang, Dan; Yu, Li (Studies in Systems, Decision and Control, 2019)
This book, written by experts in the field, is based on the latest research on the analysis and synthesis of switched time-delay systems. It covers the stability, filtering, fault detection and control problems, which are studied using the average dwell time approach. It presents both the continuous-time and discrete-time systems and provides useful insights and methods, as well as practical algorithms that can be considered in other complex systems, such as neuron networks and genetic regulatory networks, making it a valuable resource for researchers, scientists and engineers in the field of system sciences and control communities. .